Oxidation and removal of thallium and organics from wastewater using a zero-valent-iron-based Fenton-like technique. (1st June 2019) - Li, Huosheng; Li, Xiuwan; Long, Jianyou; Li, Keke; Chen, Yongheng; Jiang, Jiahao; Chen, Xiaoxuan; Zhang, Ping
Abstract: The control of thallium (Tl) pollution in wastewater is much less studied than that of other heavy metals (Cd, Hg, Pb) and metalloids (As), with even less research on the simultaneous treatment of Tl and organics. In this study, the simultaneous removal of thallium and organics from aqueous solutions using a zero-valent-iron (Fe 0 )-based Fenton-like technique was investigated. Diethylenetriaminepentaacetic acid (DTPA) was selected as the complexing agent with Tl. A response surface methodology (RSM) was employed to evaluate the influencing factors and optimize Tl and organic removal. The results reveal that the coagulation pH and Fe 0 dosage are crucial factors for simultaneous Tl and organic removal. Quadratic models were shown to be adequate for the optimization and prediction of treatment performance. Under optimized conditions of Fe 0 dosage of 3.8 g/L, [H2 O2 ]/Fe 0 molar ratio of 1.5, initial pH of 2.9, and coagulation pH of 10.5, Tl and TOC removal reached 99% and 80%, respectively. Fourier transform infrared (FT-IR) and X-ray photoelectron spectroscopy (XPS) analyses indicate that oxidation, precipitation, and adsorption contribute to Tl removal. The DTPA was degraded into small molecules that can be strongly adsorbed by the iron hydroxides under alkaline conditions. Five consecutive cyclic tests reusing Fe 0 as a catalyst maintained stable and efficient treatment performance. This Fe 0 -H2 O2 Fenton-like technique is a promising approach for the simultaneous removal of Tl and organics from wastewater. Highlights: The Fe 0 -H2 O2 Fenton-like technique is effective for simultaneous removal of Tl and DTPA. The coagulation pH is the most important factor for maximum Tl and DTPA removal. Oxidation, precipitation and adsorption are the main mechanisms for Tl removal. DTPA is degraded to small intermediates that can be adsorbed onto the iron hydroxide colloids. Fe 0 can be continuously reused for constant Fenton-like reaction.